2011
DOI: 10.1111/j.1365-2656.2011.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Using social networks to deduce whether residents or dispersers spread parasites in a lizard population

Abstract: 1. Heterogeneity of host behaviour can play an important role in the spread of parasites and pathogens around wildlife populations. Social networks have previously been suggested to represent transmission pathways within a population, but where the dynamics of host-parasite interactions are difficult to observe, networks may also be used to provide insights into transmission processes. 2. Pygmy bluetongue lizards, Tiliqua adelaidensis, occupy individual territories, live exclusively in burrows constructed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 60 publications
(128 reference statements)
1
73
0
1
Order By: Relevance
“…Network analyses have been used in community ecology studies of interacting species (e.g., pollinators, parasites, Poulin, 2010) or to identify “hub” individuals, which contribute the most to parasite spread (for instance in a lizard population in Fenner et al, 2011). Therefore, within a given population, links between vertices were randomly generated to identify vertices that have more or less connection than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Network analyses have been used in community ecology studies of interacting species (e.g., pollinators, parasites, Poulin, 2010) or to identify “hub” individuals, which contribute the most to parasite spread (for instance in a lizard population in Fenner et al, 2011). Therefore, within a given population, links between vertices were randomly generated to identify vertices that have more or less connection than expected.…”
Section: Discussionmentioning
confidence: 99%
“…AIDS networks, parasite transmission networks, etc. ), to be central probably entails a decrease in fitness, because central individuals would probably have a higher probability of infestation and mortality [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…These typically have a faecal-oral mode of transmission from one host to the next, where the first host sheds infective stages in its faeces, and the second host ingests those parasites, often in association with feeding near to the faecal deposition site (Soulsby, 1982). In the case of lizards, another method of faecal oral transmission can occur as one individual inspects the scats of another, using tongue flicks to detect olfactory signals, and potentially ingesting infective stages of the parasite on the surface of the scat (Fenner et al, 2011). We have already demonstrated that more socially connected lizards are at higher risk of infection of gut nematodes (Godfrey et al, 2009) and bacteria (Bull et al, 2012).…”
Section: Introductionmentioning
confidence: 99%